PENGARUH PROFESIONALISME AUDIT, INTENSITAS MORAL UNTUK MELAKUKAN TINDAKAN WHISTLEBLOWING (STUDI PADA KAP DI INDONESIA) - Yulita Zanaria (Universitas Muhammadiyah Metro, 2016)
Purpose – The purpose of this paper is to to investigate the influence of professionalism auditor and intensity of moral to effect on whistleblowing action of KAP in IndonesiaDesign/methodology/approach- The research method used is the population of all auditors who worked on 25 KAP in Indonesia. Sampling technique using nonprobabilitas or not random with convienience sampling method.Tool using regression analysis using F test and t test with SPSS ver.17.00. The paper ends with a set of hypotheses requiring further research. Findings – The paper finds that the professionalism auditor, intensity of moral simultaneously affect on whistleblowing action of KAP in Indonesia. professionalism auditor variable partially significant affect on whistleblowing action of KAP in Indonesia. Variable intensity of moral has an effect on whistleblowing action of KAP in Indonesia Originality/value –This paper provides influence of professionalism auditor , intensity of moral , to effect on whistleblowing action of KAP in Indonesia Keywords: Professionalism auditor , intensity of moral , effect on whistleblowing action Paper type General review